Tribological Properties of Surface-Modified Graphene Filled Carbon Fabric/Polyimide Composites. Issue 6 (3rd June 2019) - Su, Chao; Xue, Feng; Xu, Fanglin; Li, Tongsheng; Xin, Yuanshi; Wang, Mingming
Abstract: To improve the wear resistance of carbon fabric reinforced polyimide (CF/PI) composite, surface-modified graphene (MG) was synthesized and employed as a filler. The flexural strength, Rockwell hardness and thermal properties of the composites were tested. The composites were also evaluated for their tribological properties in a ring-on-block contact mode under dry sliding conditions. The results showed that the wear rate of MG reinforced CF/PI composites was reduced when compared to unfilled CF/PI composite. It was found that the 1 wt% MG filled CF/PI composites exhibited the optimal tribological properties. The worn surface, wear debris and transfer films were analyzed by scanning electron microscopy (SEM) and optical microscopy (OM) with the results helping to characterize the wear mechanism.